Al-Qur’an dan Psikologi - Muslim Afandi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
Viewed from various aspects, al-Qur'an has long talked about psychology before the West exposed this concept. Even when by definition the concept of psychology is still